The detection efficiency of the clover Ge-detectors array at the RITU-GREAT facility - Girka, Anastasiia (2015)
Absolute detection efficiency depending upon its position along the beam line is determined for three germanium detectors, that are part of the GREAT spectrometer at the RITU separator focal plane. The efficiency is determined for an energy range from 80 keV to 1400 keV for all three detectors as an array and also individually using digital electronics. The optimal position for the detector array has been defined for two configurations of the GREAT spectrometer: with planar detector and without it. The obtained results have been compared with three references: a simulation prepared especially for this setup by another student, a previous study that was carried out by applying analogue electronics and a simulation executed during the first years of the GREAT spectrometer operation.